Analisis optimasi aplikasi variasi jaringan irigasi tetes PVC ber-amiter pada lahan bertingkat untuk mendukung kegiatan pertanian di permukiman perkotaan - I D.G.J. Negara; L. Hanifah; A. Supriyadi; E. Pradjoko; A. Pracoyo (Dinamika Teknik Mesin, 2024)
This study aims to determine the effect of variations in the drip irrigation network of pvc pipes with amiter on irrigation distribution, irrigation uniformity, and soil moisture achievement on variations in irrigation duration. The test was carried out on four variations of the water level of the tower and four variations of the pvc drip irrigation network on the multi-level system, with four variations of irrigation duration t1 = 5 minutes, t2 = 10 minutes, t3 = 15 minutes and t4 = 20 minutes. The test data analyzed includes irrigation distribution data and irrigation uniformity (Cu) and soil laxative (Wt). The results of the analysis showed that with a deviation of about 1 ml, the average Cu above 97% was very good. The best drip irrigation distribution was obtained in the network of variation 3 with a range of 43.6 ml with a deviation of about 1 ml, while in variation 1 the distribution was above 210 ml with a deviation of 1-5 ml. Wt soil moisture obtained from drip irrigation variation 3 at t1-t4 duration at a depth of 20 cm, at L1 ranged from 0.69% - 21.65%, at L2 around 2.16% - 21.65%, at L3 by 2.19% - 21.68% and at L4 by 10.41% - 28.66%.  In 15 minutes of irrigation, the addition of soil lengas (w) is obtained about 7-9% with a depth of 5 cm -15 cm and at a duration of 20 minutes about 21% w is obtained for a depth of 20 cm – 25 cm.